Online Conversations About Abuse: Responses to IPV Survivors from Support Communities - Whiting, Jason B. (Journal of family violence, 2023)
PurposeIntimate partner violence (IPV) impacts the lives of millions, damaging survivors and families. Many survivors are unsure how to get help, and have limited access to resources. In recent years, those affected by IPV have turned online for answers, support, and to share their experiences. This study examined the online dialogue between survivors of violence and those who respond to their posts.MethodData consisted of 451 responses to IPV survivors on the website Reddit in a domestic violence subgroup. Responses were analyzed using a combination of grounded theory coding techniques with content analysis tools to generate categories and subcategories.ResultsThree main categories emerged from the data, including support, sharing experiences, and sharing information. The subcategories included specific types of help, advice, understanding, and were overwhelmingly positive in their tone and content.ConclusionsFindings suggest that online forums may help bridge the gap between survivors and resources. Professionals who work with IPV or create policies can use these findings to understand how to help survivors find support. This may include encouraging survivors to connect with informal supports such as family and friends, or access formal support such as hotlines, therapy, or legal counsel. The findings also suggest that more research is needed to understand what types of questions survivors of violence have, and what outcomes result from online support.